2011
DOI: 10.5483/bmbrep.2011.44.10.613
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship of Runx2 and estrogen pathway in skeletal tissues

Abstract: Two key molecules in skeletal tissues are bone formation master transcription factor Runx2 and the steroid hormone estrogen. It is well known that these two molecules play pivotal roles in bone homeostasis; however, the functional interaction between Runx2 and estrogen synthesis in skeletal tissues is largely unknown. Recent studies have indicated that there is a positive relationship between Runx2 and the estrogen biosynthesis pathway. In this review, a possible functional link between Runx2 and estrogen synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Exogenous addition of FGF4 significantly diminished DAG-induced increases in the mRNA levels of Runx2 and osterix, but not of OC and BSP. Runx2 and osterix are essential osteoblast-specific transcription factors regulating bone differentiation [42], [43]. These factors activate a repertoire of genes during differentiation of pre-osteoblasts into mature osteoblasts and osteocytes [42], [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous addition of FGF4 significantly diminished DAG-induced increases in the mRNA levels of Runx2 and osterix, but not of OC and BSP. Runx2 and osterix are essential osteoblast-specific transcription factors regulating bone differentiation [42], [43]. These factors activate a repertoire of genes during differentiation of pre-osteoblasts into mature osteoblasts and osteocytes [42], [44].…”
Section: Discussionmentioning
confidence: 99%
“…Runx2 and osterix are essential osteoblast-specific transcription factors regulating bone differentiation [42], [43]. These factors activate a repertoire of genes during differentiation of pre-osteoblasts into mature osteoblasts and osteocytes [42], [44]. Osterix is also critical for differentiation of Runx2-expressing precursors into mature and functional osteoblasts, and expression of osterix mRNA and protein is positively regulated by Runx2 [43].…”
Section: Discussionmentioning
confidence: 99%
“…The function of RUNX2 is related with several molecules and multiple pathways, such as angiogenic factor, matrix metalloproteinases (MMPs), transcription factors, the MAPK pathway, the STAT pathway and the PI3 K pathway [27], which are involved in ovarian carcinogenesis. For example, Duan et al [28] indicated that the abnormal activation on PI3 K/PKB signaling pathway may be correlated with the occurrence and development of EOC; Chakrabarty and Kondratick [29] also suggested that activation on multiple cascades of the MAPK pathway may promote the invasion and metastasis of EOC.…”
Section: Discussionmentioning
confidence: 99%
“…Although we cannot explain the mechanisms involved, it is postulated that irradiation at >2 Gy caused DNA damage and growth inhibition at early exposure times, which led to delayed recovery in cell cycle progression with the attendant stimulation of TGF-β1 expression even at 7 days post-irradiation in primary osteoblasts. Runx2, also known as core binding factor alpha 1, plays an essential role in osteoblast differentiation through transcriptional regulation of bone-specific genes (25)(26)(27)(28). A considerable number of findings suggest a relationship between TGF-β1 and Runx2 (29).…”
Section: Discussionmentioning
confidence: 99%